PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA QUIZIZZ TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS 4 SD - Kusuma, Rahmaa Ayu Erwindah; Kasriman, Kasriman (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to determine whether there is an influence of the problem-based learning model assisted by Quizizz media on the science learning outcomes of 4th grade elementary school students.  The research method used was Quantitative Experiment with the Post-test Only Control Group Design. The population in this study was all fourth-grade students at SDN Cijantung 01 Jakarta, totalling 60 students.  The sample used in this study used a saturated sample technique, namely a sampling technique when all members of the population are used as samples.  The control class is 30 students and the experimental class is 30 students.  The data analysis technique uses SPSS (Statistical Package for the Social Sciences) version 22, namely by testing validity, reliability testing, normality testing, homogeneity testing using independent sample t tests.  The average value obtained by the control class was 61.83 while the average value obtained by the experimental class was 80.83 based on the explanation above that there is an influence of the influence of the Application of the Quizizz Media Assisted Problem Based Learning Model on Science Learning Outcomes of Class 4 Elementary School Students. Keywords: Problem Based Learning; Media Quizizz; Learning Outcome